Improved cardiac outcomes by early treatment with angiotensin-converting enzyme inhibitors in becker muscular dystrophy. (14th October 2021) - Motte, L; Stalens, C; Behin, A; Ben Yaou, R; Leturcq, F; Bassez, G; Laforet, P; Fontaine, B; Ederhy, S; Masingue, M; Saadi, M; Leonard Louis, S; et al.
Abstract: Background: The latest practice guidelines from the American College of Cardiology/American Heart Association recommend the prescription of an ACE-i for patients presenting with non-ischemic cardiomyopathy when left ventricular ejection fraction (LVEF) falls below 40%. Objective: To determine if the initiation of treatment with an angiotensin-converting enzyme inhibitor (ACE-i) earlier than recommended by practice guidelines issued by professional societies improves the long-term cardiac outcomes of patients presenting with Becker muscular dystrophy (MD) cardiomyopathy. Methods: From a multicenter registry of Becker MD, we selected retrospectively patients presenting between January 1990 and April 2019 with a LVEF ≥40 and ≤49%. We used a propensity score analysis to compare the risk of a) hospitalization for management of heart failure (HF), and b) a decrease in LVEF to <35% in patients who received an ACE-i when LVEF fell below 40% (conventional treatment), versus below 50% (early treatment). Results: From the 183 patients entered in our registry, we identified 85 whose LVEF was between 40 and 49%, 51 of whom received early and 34 received conventional ACE-i treatment. Among patients with early versus conventional treatments, 2 (3.9%) versus 4 (11.8%) were hospitalized for management of HF [hazard ratio (HR) 0.151; 95% confidence interval (CI) 0.028 to 0.822; p=0.029], and 9 (17.6%) versus 10 (29.4%) had a decrease in LVEF below 35% (HR 0.290; 95% CI 0.121 to 0.694; p=0.005). Conclusions: The long-term cardiac outcome of patients presenting with Becker MD was significantly better when treatment with ACE-i was introduced after a decrease in LVEF below 50%, instead of below 40% as recommended in the current practice guidelines issued by professional societies. FUNDunding Acknowledgement: Type of funding sources: None.